Estresse e características resilientes em alunos com deficiência e TFE na UFPA - PEREIRA, Rosamaria Reo (Conselhos Federal e Regionais de Psicologia, 2019)
There are few studies dealing with the presence of stress and resilience on undergraduate students with disabilities and with specific functional disorders in higher education, which indicates the need for these two themes to be more studied and better understood in the university environment. The present study aimed to describe the sociodemographic and academic characteristics of 50 university students who participated in the study and correlate them with levels of stress and resilience. The instruments used were a semi-structured questionnaire and two scales: Perceived Stress Scale and Resilience Scale. The results were analyzed through descriptive statistics and the exploratory statistical technique. The results showed that students with high levels of stress have moderate and low levels of resilience. From this result, it was concluded the need to develop programs that aim at the maintenance of effective coping strategies in adverse situations within the academic context. It is expected that this study may contribute to the construction of institutional policies that favor the inclusion in fact of students with disabilities and with specific functional disorders at the Federal University of Pará and other higher education institutions.